2011
DOI: 10.1039/c1an15335h
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dimethylsiloxane) cross-linked carbon paste electrodes for microfluidic electrochemical sensing

Abstract: Recently, the development of electrochemical biosensors as part of microfluidic devices has garnered a great deal of attention because of the small instrument size and portability afforded by the integration of electrochemistry in microfluidic systems. Electrode fabrication, however, has proven to be a major obstacle in the field. Here, an alternative method to create integrated, low cost, robust, patternable carbon paste electrodes (CPEs) for microfluidic devices is presented. The new CPEs are composed of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 49 publications
1
38
0
2
Order By: Relevance
“…2,26 The channels were made by mixing PDMS at a ratio of 10:1 (w/w) of PDMS oligomer: cross linker followed by degassing with a vacuum pump (Vacuubrand, Germany) in a vacuum desiccator. The mixed PDMS was poured on the center of the mold surface slowly to prevent the addition of air bubbles and then baked at 80 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,26 The channels were made by mixing PDMS at a ratio of 10:1 (w/w) of PDMS oligomer: cross linker followed by degassing with a vacuum pump (Vacuubrand, Germany) in a vacuum desiccator. The mixed PDMS was poured on the center of the mold surface slowly to prevent the addition of air bubbles and then baked at 80 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…20 For electrochemically active compounds, ECD is useful because of its sensitivity and selectivity. 21-22 ECD can readily detect many molecular targets including phenols, aromatic amines, 21 glutathione, 22 reducing sugars, 23 antioxidants 24,25 and thiols 26 by controlling electrode potential and/or electrode composition. Thus, electrochemistry has been widely demonstrated as a viable detection method for a variety of flow techniques including microfluidic applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th ey are fabricated with conventional lithography or sputtering and lift -off techniques. Electrodes can be deposited directly on PDMS molds using molten solder [44,144], metal ion implantation [145], conducting composites (carbon paste fi lling) [146] or singlewalled carbon nanotubes embedded in PDMS surface [147]. Optical components (fi bers, fi lters, photodiodes), important for on-chip detection, can be integrated into a microdevice during the molding step [148] or inserted into formed microchannels [17].…”
Section: Interfacingmentioning
confidence: 99%
“…Further, we demonstrated that the PDMS: mineral oil CPEs can easily be chemically modified for the detection of biologically relevant molecules. The monitoring of thiols provides an indication of the functioning of numerous critical cellular pathways [19,20]. Traditional carbon paste electrodes can be used to detect thiols, however, they suffer from low peak currents due to poor interactions between the carbon and the thiols.…”
Section: Electrochemical Detection Methods For Cellular Stress Biomarmentioning
confidence: 99%